Tracking trash : flotsam, jetsam, and the science of ocean motion - Burns, Loree Griffin (Boston : Houghton Mifflin, 2007)
Describes the work of a man who tracks trash as it travels great distances by way of ocean currents.
Includes bibliographical references (p. 56) and index.
A Junior Library Guild selection
Keywords: Ocean currents -- Juvenile literature; Marine debris -- Juvenile literature; Ocean currents; Pollution